Theatre Adaptations in the cinema by Pedro Almodóvar: Cocteau, Williams and Lorca - De la Torre Espinosa, Mario (2018)
The cinema by Pedro Almodóvar is considered as theatrical. As main reason, the continued use of theatre intertexts. The main goal of this article is study the modus operandi of the Spanish filmmaker in the adaptation of theatre plays in his cinema. We will analyze the mise-en-scene of the plays La Voix Humaine by Jean Cocteau, A Streetcar Named Desire by Tennessee Williams, and Bodas de Sangre and Yerma by Federico García Lorca in the films La ley del deseo, Mujeres al borde de un ataque de nervios and Todo sobre mi madre. According the classifications by Anxo Abuín and José Antonio Pérez Bowie, we conclude that the artifice of this cinema is inserted in a theatrum mundi vision, with an evident performativity.